Analisis Kesuksesan website kemahasiswaan universitas dinamika dengan menggunakan model delone and mclean berdasarkan presepsi mahasiswa - Kurniawan, Ramdhani; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Dinamika University (UNDIKA) is one of the universities which is located in Surabaya. Dinamika University has two faculties, namely the Faculty ofÂ Industry Technology (FTI) and the Faculty of Economy and Business (FEB) which are divided into 9 field of study departments namely 6 departments in the FTI including S1 of Information System, S1 of Computer Technique, S1 of Visual Communication Design, SI of Product Design, DIV of Film and Television Production, DIII of Information System and 3 in the FEB including S1 of Management, S1 of Accounting, and DIII of Office Administration. One of the the parts which exists in UNDIKA in providing services is the part of the university students. The part of the university student itself works at the management of the activities of councelling of soft skills by providing mediums and facilities as the organizational place of the students. To support its taks, the part of the university student has a website which functions as the media of spreading information to the students. Based on the results of the interview from the survey with the students, up to now, the website kemahasiswaan.dinamika.ac.id has never done any evaluation about the qualities of the system, information and services of the website. With the sampel of 94 respondents of Dinamika University students, it can be concluded that the quality of information influences the satisfaction of the users, the quality of information, and the quality of services influences the use, the quality of system influences the satisfaction of the users, the use influences the satisfaction of the users, and the use influences the clean benefit.